2019
DOI: 10.1186/s12909-019-1824-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bronchoscopy guidance system for bronchoscopy training, a randomized controlled trial

Abstract: BackgroundConventional training in bronchoscopy is performed either on patients (apprenticeship model) or phantoms. While the former is associated with increased rate of patient complications, procedure time, and amount of sedation, the latter does not offer any form of feedback to the trainee. This paper presents a study which investigates whether a bronchoscopy guidance system may be a helpful tool for training of novice bronchoscopists.MethodsA randomized controlled study with 48 medical students was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…A bronchoscope is employed to both visualise and remove samples from suspected lung tissue and is essential for the diagnosis of airway lesions and parenchymal lung disorders. In a detailed review by Fullmann et al, 69 its utility for the diagnosis of peripheral pulmonary nodules is shown to be limited. Since lung tissue is heterogeneous and affects the early detection of tumors, tissue biopsies may not be unambiguous.…”
Section: Bronchoscopymentioning
confidence: 99%
“…A bronchoscope is employed to both visualise and remove samples from suspected lung tissue and is essential for the diagnosis of airway lesions and parenchymal lung disorders. In a detailed review by Fullmann et al, 69 its utility for the diagnosis of peripheral pulmonary nodules is shown to be limited. Since lung tissue is heterogeneous and affects the early detection of tumors, tissue biopsies may not be unambiguous.…”
Section: Bronchoscopymentioning
confidence: 99%
“…In the traditional teaching method (“see one, do one, teach one”), apprentices perform the procedure directly on the patient under the supervision of experienced professionals. Although this method is commonly regarded as safe, there is a risk of complications, especially in the early stages of learning, due to the apprentice's inexperience and stress 2 …”
Section: Introductionmentioning
confidence: 99%